Life scripts for emotionally charged autobiographical memories: A cultural explanation of the reminiscence bump - Haque, S.; Hasking, Penelope (Psychology Press, 2010)
Two studies examined the ability of the life script account to explain the reminiscence bump for emotionally charged autobiographical memories among Malaysian participants. In Study 1 volunteers, aged 50-90 years, participated in a two-phased task. In the first phase, participants estimated the timing of 11 life events (both positive and negative) that may occur in a prototypical life course within their own culture. Two weeks later the participants retrieved the same set of events from their lives and reported how old they were when those events occurred. In the second study 92 undergraduate students produced life scripts for the same 11 events. The findings revealed reminiscence bumps in both life script and retrieval curves for the memories judged happiest, most important, most in love, and most jealous. A reminiscence bump was also noted for success, although this was later in the lifespan than other reminiscence bumps. It was suggested that the life scripts can be used as an alternative account for the reminiscence bump, for highly positive and occasionally for negative autobiographical memories.